2019
DOI: 10.3340/jkns.2019.0015
|View full text |Cite
|
Sign up to set email alerts
|

Stereoelectroencephalography in Pediatric Epilepsy Surgery

Abstract: Stereoelectroencephalography (SEEG) is an invasive technique used during the surgical management of medically refractory epilepsy. The utility of SEEG rests in its ability to survey the three-dimensional organization of the epileptogenic zone as well as nearby eloquent cortices. Once concentrated to specialized centers in Europe and Canada, the SEEG methodology has gained worldwide popularity due to its favorable morbidity profile, superior coverage of deep structures, and ability to perform multilobar explora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 97 publications
0
15
0
Order By: Relevance
“…7,10,32 SEEG can also monitor deep or medial structures directly and precisely, makes monitoring of multiple lobes or hemispheres more feasible, and avoids craniotomy altogether for patients who will undergo minimally invasive surgery or no surgery. 25,[33][34][35][36] As a result, the use of SEEG has become widespread in North American pediatric epilepsy centers over the past decade. 1,23,24 However, most centers avoid SEEG in the very young, especially those younger than age 2.…”
Section: Discussionmentioning
confidence: 99%
“…7,10,32 SEEG can also monitor deep or medial structures directly and precisely, makes monitoring of multiple lobes or hemispheres more feasible, and avoids craniotomy altogether for patients who will undergo minimally invasive surgery or no surgery. 25,[33][34][35][36] As a result, the use of SEEG has become widespread in North American pediatric epilepsy centers over the past decade. 1,23,24 However, most centers avoid SEEG in the very young, especially those younger than age 2.…”
Section: Discussionmentioning
confidence: 99%
“…10 Well-established surgical options for pediatric MRE include resection, disconnection, neurostimulation, invasive monitoring via subdural grid (SDG) electrodes, or some combination thereof. 11 In many cases, resection is effective in disrupting the epileptogenic zone, controlling patient seizures, and improving quality of life. [11][12][13][14][15][16][17] However, open resections are invasive, associated with risks, and often unsuitable for patients with deep-seated foci.…”
Section: Clinical Articlementioning
confidence: 99%
“…Recent studies have shown that advances in imaging, planning, and robotic‐assisted surgery have made SEEG a safe tool in children, with low rates of adverse events such as hemorrhage and infection 3‐13 . Despite these advances, the rate of seizure‐free outcomes following SEEG‐guided resective surgery stands at 50%‐67% 4,9,13‐15 …”
Section: Introductionmentioning
confidence: 99%